Life history and status of Shortnose Sturgeon (Acipenser brevirostrum LeSueur, 1818). (December 2016) - Kynard, B.; Bolden, S.; Kieffer, M.; Collins, M.; Brundage, H.; Hilton, E. J.; Litvak, M.; Kinnison, M. T.; King, T.; Peterson, D.
Summary: Shortnose Sturgeon = SNS ( Acipenser brevirostrum ) is a small diadromous species with most populations living in large Atlantic coast rivers and estuaries of North America from New Brunswick, Canada, to GA, USA. There are no naturally land‐locked populations, so all populations require access to fresh water and salt water to complete a natural life cycle. The species is amphidromous with use of fresh water and salt water (the estuary) varied across the species range, a pattern that may reflect whether freshwater or saltwater habitats provide optimal foraging and growth conditions. Migration is a dominant behaviour during life history, beginning when fish are hatchling free embryos (southern SNS) or larvae (northeastern and far northern SNS). Migration continues by juveniles and non‐spawning adult life stages on an individual time schedule with fish moving between natal river and estuary to forage or seek refuge, and by spawning adults migrating to and from riverine spawning grounds. Coastal movements by adults throughout the range (but particularly in the Gulf of Maine = GOM and among southern rivers) suggest widespread foraging, refuge use, and widespread colonization of new rivers. Colonization may also be occurring in the Potomac River, MD–VA–DC (mid‐Atlantic region). Genetic studies (mtDNA and nDNA) identified distinct individual river populations of SNS, and recent range‐wide nDNA studies identified five distinct evolutionary lineages of SNS in the USA: a northern metapopulation in GOM rivers; the Connecticut River; the Hudson River; a Delaware River–Chesapeake Bay metapopulation; and a large southern metapopulation (SC rivers to Altamaha River, GA). The Saint John River, NB, Canada, in the Bay of Fundy (north of the GOM), is the sixth distinct genetic lineage within SNS. Life history information from telemetry tracking supports the genetic information documenting extensive movement of adults among rivers within the three metapopulations. However, individual river populations with spawning adults are still the best basal unit for management and recovery planning. The focus on individual river populations should be complemented with attention to migratory processes and corridors that foster metapopulation level risks and benefits. The species may be extirpated at the center of the range, i.e., the mid‐Atlantic region (Chesapeake Bay, MD–VA, and probably, NC), but large rivers in VA, including the James and Potomac rivers, need study. The largest SNS populations in GOM and northeastern rivers, like the Kennebec, Hudson, and Delaware rivers, typically have tens of thousands of adults. This contrasts with southern rivers, where rivers typically have much fewer (<2500) adults, except for the Altamaha River (>6000 adults). River damming in the 19th and 20th Centuries extirpated some populations, and also, created two dysfunctional segmented populations: the Connecticut River SNS in CT–MA and the Santee‐Cooper rivers–Lake Marion SNS in SC. The major anthropogenic impact on SNS in marine waters is fisheries bycatch. The major impacts that determine annual recruitment success occur in freshwater firstly, where adult spawning migrations and spawning are blocked or spawning success is affected by river regulation and secondly, where poor survival of early life stages is caused by river dredging, pollution, and unregulated impingement‐entrainment in water withdrawal facilities. Climate warming has the potential to reduce abundance or eliminate SNS in many rivers, particularly in the South. In 1998, the National Marine Fisheries Service (NMFS) recommended management of 19 rivers as distinct population segments (DPSs) based on strong fidelity to natal rivers. A Biological Assessment completed in 2010 reaffirmed this approach. NMFS has not formally listed DPSs under the ESA and the species remains listed as endangered range‐wide in the USA.